Parents of Children with Autism An Ethnography - Wolfe, Juliette de. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
In a readable and highly accessible ethnographic account that is shaped by the stories of families and the voices of parents, De Wolfe examines how parents of children with autism navigate the educational and medical systems, understand their own and their children's bodies, and support and educate one another.